Fabrication of composite FO hollow fiber membranes by co-spinning process – preliminary investigation on properties of the support layer - Cwa, Jackson Xing Long (2010)
Forward (or direct) osmosis (FO) recently received growing attention from numerous disciplines, among them water reclamation. FO offers the advantage of the same high rejection of a wide range of contaminants without the high energy consumption and membrane-fouling propensities of traditional pressure-driven membrane processes. The potential for FO process being used for water reclamation as a much viable alternative than RO process is thus very high. One of the challenges deterring the full exploration of FO potential in this area is the limited number of commercially available FO membranes with high water permeation and superior salt separation performance. The ultimate aim is to fabricate composite hollow fiber FO membranes in a one step co-extrusion and phase inversion process as an alternative to current available membranes not optimised for FO processes. As the foundation for this research, this Final Year Project is but one of the projects carried out in a series, focusing on the support layer of the composite hollow fiber FO membrane